2018
DOI: 10.1186/s12885-018-4649-2
|View full text |Cite
|
Sign up to set email alerts
|

LIM and SH3 protein 1 regulates cell growth and chemosensitivity of human glioblastoma via the PI3K/AKT pathway

Abstract: BackgroundLIM and SH3 protein 1 (LASP1) is upregulated in several types of human cancer and implicated in cancer progression. However, the expression and intrinsic function of LASP1 in glioblastoma (GBM) remains unclear.MethodOncomine and The Cancer Genome Atlas (TCGA) database was analyzed for the expression and clinical significance of LASP1 in GBM. LASP1 mRNA and protein level were measured by qRT-PCR and western blotting. The effect of LASP1 on GBM proliferation was examined by MTT assay and colony formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 23 publications
2
32
0
Order By: Relevance
“…18 Previous studies prove that LASP1 regulates cell proliferation in glioblastoma and gallbladder cancer through the PI3K/Akt pathway. 13,20 Our results showed that LASP2 knockdown significantly suppressed PI3K/Akt pathway. 740Y-P, abolished the inhibitory effects of LASP2 knockdown on cervical cancer, implying that the effects of LASP2 were mediated by the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 70%
“…18 Previous studies prove that LASP1 regulates cell proliferation in glioblastoma and gallbladder cancer through the PI3K/Akt pathway. 13,20 Our results showed that LASP2 knockdown significantly suppressed PI3K/Akt pathway. 740Y-P, abolished the inhibitory effects of LASP2 knockdown on cervical cancer, implying that the effects of LASP2 were mediated by the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 70%
“…Decreased pAKT1-S473 phosphorylation after LASP1 depletion has been observed before in several tumor cell lines, glioblastoma [21], gall bladder [22] and nasopharyngeal carcinoma [23], while LASP1 overexpression induces phosphorylation in colorectal cancer cells [24] and non-small cell lung cancer [25]. However, the underlying mechanisms are still controversial.…”
Section: Introductionmentioning
confidence: 87%
“…LIM and SH3 protein 1 (LASP1), a structural scaffolding protein and adhesion adaptor protein, was initially identified in breast cancer and was located at 17q12 [19]. Previous studies showed that LASP1 was upregulated in many malignant tumors including nasopharyngeal carcinoma, breast cancer, glioblastoma and colorectal cancer and contributed to tumor proliferation, invasion and metastasis [20][21][22][23]. In addition, LASP1 is upregulated in pancreatic ductal adenocarcinoma and is essential for HIF1α-induced invasion and metastasis [24].…”
Section: Introductionmentioning
confidence: 99%